METHODS AND TECHNIQUES FOR DEVELOPING STUDENTS’ CREATIVE THINKING IN TEACHING FOREIGN LANGUAGES - AKHMEDOVA, Laylokhon Tolibjonovna (The Lingua Spectrum, 2025)
The article examines effective methods, techniques, and exercises aimed at developing students’ creative thinking in the process of teaching foreign language. Various theoretical approaches to defining creativity are analyzed, including ideas proposed by Dewey, Sternberg, Guilford, Maslow, Paul, and other scholars. Special attention is given to the distinction between convergent and divergent thinking and their role in creative activity. The paper presents practical tools such as dictogloss, associative techniques, the PMI method, the “Six Thinking Hats,” and the Dreamer–Realist–Critic model, as well as creative storytelling and poetic Diamond forms. The proposed methods foster students’ analytical, logical, communicative, and creative abilities and contribute to increasing motivation, independence, and responsibility in the learning process. The study highlights the importance of integrating creative thinking technologies into foreign language education to enhance the effectiveness of learning and promote active student engagement.